Analysis of Dynamic PD Control Performance Compared to Standard PD in Track Follower Vehicle - Dalmazo, Luan Matheus Trindade; Hishida, Gabriel N.; Silva, Allan Cedric Gouvea Bruglimann Alves Da; Valadares, Tiago Serique; Sepulveda, Rian Marcos; Midzuno, Seijiro Yanagiya; Santos, Ketlyn Dos; Todt, Eduardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This paper compares the golden standard PD and the alternative dynamic PD, two control systems that can be used for line follower robots. In the dynamic PD, the parameters change over time, allowing local optimizations. A test track was made to measure the performance of both controllers. The total elapsed time that the robot took to complete the circuit and the stability in the trajectory were used as evaluation metrics to compare them. The robot’s most relevant parts and components used for the tests are also detailed. Finally, we demonstrate that dynamic PD is an attractive alternative to complete the track in a shorter time and with higher speeds.